Preliminary studies on the effects of d-limonene to workers of the leaf-cutting ant Atta sexdens rubropilosa and its implications for control - Verza, Sandra S. [UNESP]; Nagamoto, Nilson S. [UNESP]; Forti, Luiz C. [UNESP]; Noronha Jr., Newton C. [UNESP] (My University, 2011)
To better understand the potential of controlling of leaf-cutting ants, a serious pest, with conventional synthetic insecticides as well as botanical pesticides, we propose to evaluate the effect of d-limonene on attractiveness and rejection of citric pulp to the leaf-cutting ant Atta sexdens rubropilosa Forel. Five treatments were adopted that consisted of fragments of filter paper impregnated with various concentrations of d-limonene and with organic extract of citrus pulp. The number of fragments loaded by the ants in the foraging arena and transported to the fungus garden and of fragments rejected in the refuse chamber was counted. It has been shown that d-limonene provoked concentration-dependent reduction of attractiveness response to A. sexdens rubropilosa workers. No rejection of loaded fragment was observed. We discussed the relationship between substrate selection and its repellent compounds, and also that a repellent substrate component can be overcome or masked by the overall odour of attractive substrates. Also, the repellence of the toxic bait AI (active ingredient) and its implication in control efficiency and the use of repellent AIs in other control methods, emphasizing nebulization, are discussed.
Keywords: Attini; Chemical control; Citrus pulp; Insecticide; Repellence